2018
DOI: 10.1080/19490976.2017.1405209
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the gut microbiota by metformin improves metabolic profiles in aged obese mice

Abstract: The gut microbiota is a contributing factor in obesity-related metabolic disorders. The effect of metformin on the gut microbiota has been reported; however, the relationship between the gut microbiota and the mechanism of action of metformin in elderly individuals is unclear. In this study, the effect of metformin on the gut microbiota was investigated in aged obese mice. The abundance of the genera Akkermansia, Bacteroides, Butyricimonas, and Parabacteroides was significantly increased by metformin in mice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
127
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 52 publications
16
127
0
7
Order By: Relevance
“…A high level of IVIVC at the phylum level, especially for day 14 samples, was indicated with Pearson's correlation of r = 0.93 ± 0.02 ( Figure 3B). Furthermore, at the genus level, we observed a consistent increase in the genera Akkermansia, Bacteroides and Parabacteroides ( Figure 3C) under both in vitro and in vivo conditions, the in vivo change was agreement with the previously reported studies 5,41,42 . At the species level, three separate groups of PLS-DA analyses were performed by comparing untreated microbiome versus microbiome following in vivo 14-and 28-day and in vitro 24 hr metformin treatment, respectively.…”
Section: Evaluation Of In Vitro-in Vivo Correlation Of Microbial Respsupporting
confidence: 92%
See 1 more Smart Citation
“…A high level of IVIVC at the phylum level, especially for day 14 samples, was indicated with Pearson's correlation of r = 0.93 ± 0.02 ( Figure 3B). Furthermore, at the genus level, we observed a consistent increase in the genera Akkermansia, Bacteroides and Parabacteroides ( Figure 3C) under both in vitro and in vivo conditions, the in vivo change was agreement with the previously reported studies 5,41,42 . At the species level, three separate groups of PLS-DA analyses were performed by comparing untreated microbiome versus microbiome following in vivo 14-and 28-day and in vitro 24 hr metformin treatment, respectively.…”
Section: Evaluation Of In Vitro-in Vivo Correlation Of Microbial Respsupporting
confidence: 92%
“…Metformin is a widely prescribed drug for treating type 2 diabetes and it has been reported that in human 30% of the oral dose can be recovered in ers he for in feces 40 . Several studies have focused on the effect of metformin on gut microbiota composition and functions 5,6,41 . For these reasons, we employed metformin to validate our MiPro model against in vivo studies by investigating the impact of metformin exposure on gut microbial communities in mice and in our model.…”
Section: Evaluation Of In Vitro-in Vivo Correlation Of Microbial Respmentioning
confidence: 99%
“…is colonised by a unique microbial community, including species such as Bacteroides fragilis and Akkermansia muciniphila 11,12 . The importance of A. muciniphila is only starting to emerge in connection with several diseases: it is most beneficial to the host, although an excess has been linked to pathologies such as multiple sclerosis 13 and Parkinson's disease 14 .…”
mentioning
confidence: 99%
“…Additionally, members of the Lachnospiraceae and Erysipelotrichaceae families have previously been suggested to be associated with microbe TMA generation and development of atherosclerosis (Qiu, Tao, Xiong, Yu, & Wei, 2018). These species have been suggested as playing a role in inhibiting obesity as well as improving intestinal barrier function, possibly through interaction with host intestinal epithelial cells via mucoprotein(Berry et al, 2012;Depommier et al, 2019;Lee et al, 2018).The differences in the gut microbial species from different experimental groups were further defined using LEfSe analysis (Figure 4). The composition of the gut microbiota at the phylum and genus levels induced by the experimental diets is shown in Figure 3.…”
mentioning
confidence: 99%
“…without AMPK inhibition). These species have been suggested as playing a role in inhibiting obesity as well as improving intestinal barrier function, possibly through interaction with host intestinal epithelial cells via mucoprotein(Berry et al, 2012;Depommier et al, 2019;Lee et al, 2018).The differences in the gut microbial species from different experimental groups were further defined using LEfSe analysis (Figure 4). Species from Firmicutes phylum, Dubosiella, Chlamydia, Enterorhabdus, and Clostridium were identified to be significantly enriched in the mice fed with a red meat diet, potentially indicating a relatively unhealthy gut environment as these species have been associated with dysbiosis or pathogenicity (Kociolek & Gerding, 2016; Leclercq et al, 2017; Zhang et al, 2018).…”
mentioning
confidence: 99%